2019
DOI: 10.1055/s-0039-1700549
|View full text |Cite
|
Sign up to set email alerts
|

Tuft Cells: A New Player in Hirschsprung's Disease

Abstract: Introduction “Tuft” cells, also known as brush or caveolated cells, are characteristically fusiform shaped, with a distinct apical “tuft” of microvilli extending into the lumen. Double cortin-like kinase 1 (DCLK1) is a microtubule kinase and is a specific marker of intestinal tuft cells. DCLK1-positive tuft cells have been shown to play a key role in gastrointestinal chemosensation, inflammation, and neurotransmission. DCLK1 and Choline acetyltransferase (ChAT), the enzymes responsible for acetylcholine produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, acetylcholine derived from tuft cells and nonneuronal sources has recently been implicated in the regulation of airway smooth muscle tone. 58 Whereas bronchiolar hyperresponsiveness and allergic inflammation are inhibited by vagotomy of parasympathetic nerves in the lungs in a canine model 59 (suggesting that neuronal acetylcholine plays an essential role in the pathogenesis of asthma), acetylcholine derived from tuft cells is still thought to play a role in the pathogenesis of pulmonary diseases, Hirschsprung's disease 60 and several cancers. 61,62 Given that cholinergic bronchoconstriction is an important clinical feature of asthma, tuft cells and innate immune mechanisms of acetylcholine production could provide a new target for novel therapeutic interventions.…”
Section: Acetylcholine Released By Tuft Cells Is Implicated In the Pathogenesis Of Pulmonary Diseasesmentioning
confidence: 99%
“…However, acetylcholine derived from tuft cells and nonneuronal sources has recently been implicated in the regulation of airway smooth muscle tone. 58 Whereas bronchiolar hyperresponsiveness and allergic inflammation are inhibited by vagotomy of parasympathetic nerves in the lungs in a canine model 59 (suggesting that neuronal acetylcholine plays an essential role in the pathogenesis of asthma), acetylcholine derived from tuft cells is still thought to play a role in the pathogenesis of pulmonary diseases, Hirschsprung's disease 60 and several cancers. 61,62 Given that cholinergic bronchoconstriction is an important clinical feature of asthma, tuft cells and innate immune mechanisms of acetylcholine production could provide a new target for novel therapeutic interventions.…”
Section: Acetylcholine Released By Tuft Cells Is Implicated In the Pathogenesis Of Pulmonary Diseasesmentioning
confidence: 99%
“…However, the identification and characterization of TCs in the human intestinal tract based on marker expression is still awaiting consensus. Two studies (42,43) describe a population of human colonic DCLK1 + TCs, however, Leppänen et al (44) reported that human colonic epithelial DCLK + cells have a morphology similar to absorptive enterocytes rather than a classical TC shape, thus questioning whether DCLK1 marks human TCs. In this context we recently tested a commercially available antibody (ab31704) on human colonic material, and failed to obtain convincing immunolabeling for DCLK1 (23), a conclusion also reached by Banerjee et al (40).…”
Section: Identification Of Human Intestinal Tcsmentioning
confidence: 99%
“…However, the identification and characterization of TCs in the human intestinal tract based on marker expression is still awaiting consensus. Two studies ( 42 , 43 ) describe a population of human colonic DCLK1 + TCs, however, Leppänen et al. ( 44 ) reported that human colonic epithelial DCLK + cells have a morphology similar to absorptive enterocytes rather than a classical TC shape, thus questioning whether DCLK1 marks human TCs.…”
Section: Intestinal Tcs and Originmentioning
confidence: 99%
“…With increasing evidence highlighting the role of ACh as an autocrine and paracrine hormone, cholinergic targets have drawn widespread attention in pulmonary diseases ( Meurs et al, 2013 ; Voisin et al, 2017 ), Hirschsprung’s disease ( O’Donnell et al, 2020 ) and cancers ( Westphalen et al, 2014 ; Schütz et al, 2015 ; Pozo et al, 2018 ; Friedman et al, 2019 ; Goto et al, 2019 ). Tuft cells, considered as a crucial non-neuronal ACh source, have also been discussed in several disease models.…”
Section: Potential Clinical Applicationmentioning
confidence: 99%
“…A recent study on Hischsprung’s disease (HSCR) suggested a new role of tuft cells ( O’Donnell et al, 2020 ). Using immunolabeling and qRT-PCR analysis, O’Donnell et al (2020) observed a decrease of DCLK1 + tuft cells in human HSCR tissue specimens. The authors supposed that the reduction of tuft cells is, in part, responsible for the bowel dysmotility.…”
Section: Potential Clinical Applicationmentioning
confidence: 99%